2013
DOI: 10.1007/s10802-013-9754-8
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity Moderates Promotive Environmental Influences on Adolescent Delinquency: A Comparison Across Family, School, and Neighborhood Contexts

Abstract: The present study examined moderating effects of impulsivity on the relationships between promotive factors from family (family warmth, parental knowledge), school (school connectedness), and neighborhood (neighborhood cohesion) contexts with delinquency using data collected from N = 2,978 sixth to eighth graders from 16 schools surrounding a major city in the Midwestern United States. More than half of the respondents were non-Caucasian (Mage = 12.48; 41.0% male). Multilevel modeling analyses were conducted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 51 publications
2
14
1
1
Order By: Relevance
“…In particular, greater child impulsivity is concurrently and longitudinally associated with poorer monitoring during pre-adolescence (Flannery, Vazsonyi, Torquati & Fridrich, 1994;Neumann et al, 2010). The effect of child impulsivity on parental monitoring appears more prevalent in the context of at-risk familial factors, such as neighborhood poverty and single parent family structure (Chen & Jacobson, 2013;Neumann et al, 2010). Poorer monitoring is also associated with parental characteristics including parental substance abuse (Chassin, Curran, Hussong, & Colder, 1996).…”
Section: Parental Monitoringmentioning
confidence: 99%
“…In particular, greater child impulsivity is concurrently and longitudinally associated with poorer monitoring during pre-adolescence (Flannery, Vazsonyi, Torquati & Fridrich, 1994;Neumann et al, 2010). The effect of child impulsivity on parental monitoring appears more prevalent in the context of at-risk familial factors, such as neighborhood poverty and single parent family structure (Chen & Jacobson, 2013;Neumann et al, 2010). Poorer monitoring is also associated with parental characteristics including parental substance abuse (Chassin, Curran, Hussong, & Colder, 1996).…”
Section: Parental Monitoringmentioning
confidence: 99%
“…By comparison, residence in neighborhoods that are low in resources is related to lower self-control (Teasdale & Silver, 2009) and higher externalizing problems among youth (Zalot, Jones, Forehand, & Brody, 2007). Furthermore, youth with lower self-control may, in turn, be more susceptible to risk and protective factors in their neighborhood contexts (e.g., Chen & Jacobson, 2013;Lynam et al, 2000;Meier, Slutske, Arndt, & Cadoret, 2008).…”
Section: Neighborhood Processes and Self-controlmentioning
confidence: 99%
“…Other investigations and a recent meta-analysis of 17 studies found that family influence had greater effects on curbing girls' marijuana use (e.g., Choquet et al, 2008;Lac & Crano, 2009). Still, others have reported no gender difference in the effect of family monitoring on substance use (Chen & Jacobson, 2013;Fagan et al, 2011). Studies of peer effects on substance use have found similar discrepancies in whether boys or girls are more susceptible to peer influence.…”
Section: Differential Effects Of Family Monitoring and Antisocial Peementioning
confidence: 99%